While studying Module Theory, I've been stuck on this exercise; any help would be very welcome:

Let $0 \longrightarrow M_1 \longrightarrow M_2 \longrightarrow ... \longrightarrow M_{n-1} \longrightarrow M_n \longrightarrow 0$ be an exact sequence of $R$-modules such that $lh(M_i)$, the lenght of $M_i$, is finite for all $i \in \{1,...,n\}$. Show that


I feel that one could argument by induction (on $n$), but I don't see how.

  • $\begingroup$ Do you know the result in the case of short exact sequences? $\endgroup$ – Eric Wofsey Nov 2 '20 at 18:57
  • $\begingroup$ Hi, Eric. Actually no, I do not $\endgroup$ – Ranopano Nov 2 '20 at 18:58
  • 1
    $\begingroup$ The general case is easy to deduce from the case of short exact sequences; see math.stackexchange.com/questions/2959644/… for instance (that's for the case $n=4$, but the argument easily generalizes). $\endgroup$ – Eric Wofsey Nov 2 '20 at 18:59
  • $\begingroup$ Induction ist IMHO a good idea to start with ... After the verification for $n=1$ and assuming for a certain $k$ such that $1 \le k \le n$ that you have $\sum^k_{i=1}(-1)^ilh(M_i)=0$, what would you know about $\sum^{k+1}_{i=1}(-1)^ilh(M_i)$ except that $\sum^{k+1}_{i=1}(-1)^ilh(M_i) = (-1)^{k+1}lh(M_{k+1}) + \sum^k_{i=1}(-1)^ilh(M_i) = (-1)^{k+1}lh(M_{k+1})$ because $\sum^k_{i=1}(-1)^ilh(M_i)=0$? Can you prove that $(-1)^{k+1}lh(M_{k+1}) = 0$ which means that $lh(M_{k+1}) = 0$? This is rather a comment than an answer. That's why I am going to delete my answer below... $\endgroup$ – Noureddine Ouertani Nov 2 '20 at 19:13

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Browse other questions tagged or ask your own question.